Studi Kebutuhan Modul Pembelajaran Sastra berbasis Kearifan Lokal di SMK - Kusuma, Marchell Teja; Burhanudin, Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to identify and analyze the needs of local wisdom-based literature learning modules in Vocational High Schools (SMK). The approach used is descriptive qualitative with data collection techniques in the form of in-depth interviews, observations, and questionnaires to teachers and students. The results of the study indicate that literature learning in schools is not optimal because most teachers still rely on text teaching materials and have not consistently linked the material to local culture. Meanwhile, student responses showed high enthusiasm for literature learning that is contextualized with their regional life and culture. The use of learning modules is considered capable of improving the structure, interactivity, and relevance of learning materials. Therefore, the development of local wisdom-based literature modules is a strategic step to strengthen cultural identity, increase learning motivation, and make the learning process more meaningful.